Variable Number Tandem Repeats in the promoter region of prostacyclin synthase gene in choline deficient rats. - Denninghoff, Valeria Cecilia (2010)
Weanling Sprague-Dawley rats were fed on a choline-deficient diet with hydrogenated vegetable oil and corn oil as lipids develop acute renal failure. Pathogenesis of the latter is controversial and an ischemic mechanism has been proposed. Arachidonic acid derivatives are involved in the regulation of vascular tonus. Vasospasm could be due to an increase in tromboxane A2-mediated vasoconstriction or to a decrease in prostacyclin-induced vasodilatation. Enzymes involved in the synthesis of both compounds are tromboxane A2- and prostacyclin-synthase respectively. The aim of this study was to identify the variable number tandem repeats (VNTR) in the promoter region of prostacyclin synthase gene and verify if there exists a relationship between the occurrence of VNTR in those choline-deficient rats which die because of acute renal failure and those which do not. We verified the presence of the VNTR in the prostacyclin synthase rat gene, but we did not find any difference in the molecular weight of the alleles between experimental and control rats. Renal reparation of the acute kidney injury due to choline deficiency in some rats is not related with differences in VNTR in the promoter region of the prostacyclin synthase gene. Weanling Sprague-Dawley rats fed a choline-deficient diet with hydrogenated vegetable oil and corn oil as lipids develop acute renal failure. Its pathogenesis is controversial. The ischemic mechanism has been proposed. Derivatives from arachidonic acid are involved in the regulation of vascular tone. Vasospasm could be due to an increase in vasoconstriction mediated by tromboxane A2 or a decrease in vasodilatation by prostacyclin. Enzymes involved in the synthesis of them are tromboxane A2 and prostacyclin synthase respectively. The aim of this study is to identify the variable number tandem repeats (VNTR) in the promoter region of prostacyclin synthase gene and verify if there exists a relationship between the VNTR and those rats which dye as a consequence of acute renal failure due to choline deficiency and those which do not die. The VNTR presence was detected by molecular methods. We verified the presence of the VNTR in the prostacyclin synthase rat gene. We did not find difference in the molecular weight of the alleles between experimental and control rats. Renal reparation of the acute kidney injury due to choline deficiency in Sprague-Dawley rats is not related with differences in prostacyclin synthase VNTR, in the promoter region of this gene.